What do gravitational wave detectors say about polymer quantum effects?. Issue 11 (1st November 2022) - Garcia-Chung, Angel; Carney, Matthew F.; Mertens, James B.; Parvizi, Aliasghar; Rastgoo, Saeed; Tavakoli, Yaser
Abstract: We compute the expected response of detector arms of gravitational wave observatories to polymerized gravitational waves. The mathematical and theoretical features of these waves were discussed in our previous work. In the present manuscript, we find both perturbative analytical, and full nonperturbative numerical solutions to the equations of motion of the detector arms using the method of geodesic deviations. These results show the modifications to both frequency and amplitude of the signal measured by the detector. Furthermore, we study the detectability of these signals in LISA by analyzing the modes in the frequency space.